ANALISIS KADAR ASAM ASETAT HASIL FERMENTASI ECO-ENZYME DARI KULIT JERUK BALI (Citrus maxima Merr.) DAN POTENSINYA SEBAGAI ANTIOKSIDAN DENGAN METODE ALKALIMETRI DAN DPPH - bungamri sembiring (Jurnal Penelitian Farmasi & Herbal, 2022)
The garbage problem is a very important problem because it has the potential to damage the balance of the environmental ecosystem. Many studies have been carried out on the content of active compounds in grapefruit peel, but there are differences in sampling locations, types of solvents for extraction, differences in treatment and testing. In the discovery of Eco-enzyme fermentation solution product, Dr. Rosukon Poompanvong to help local farmers to obtain better yields while being friendly to the environment. Eco-Enzyme is a popular fermented fruit peel organic waste which has been developed because it is very practical, economical, and environmentally friendly. Utilization of fruit peels into Eco-Enzyme is an evolution of science in the health sector. This study aims to determine the Eco-Enzyme fermentation process from pomelo peel and Eco-Enzyme acetic acid levels and their potential as antioxidants with experimental research using Eco-Enzyme sample solution with FeCl3 solution as a qualitative test indicator for Eco-Enzyme samples. Quantitative test using 1-2 drops of Eco-Enzyme sample solution 0,1 M NaOH standard solution and phenolphthalein indicator solution in alkalimetric titration and DPPH method with DPPH solution using UV-Vis spectrophotometer. From the results of qualitative research, the results of Eco-Enzyme fermentation are in the form of a light brown solution, have a brick red precipitate, and there is a brick red precipitate. The results of quantitative research on alkalimetric titration of Eco-Enzyme fermentation, there is an acetic acid level of 7.5% per one gram of pomelo peel, and the DPPH method on the fermented Eco-Enyme solution with an IC50 value of 9.418075752 ppm, which means it has very strong antioxidant potential. Eco-enzyme sample solution has acetic acid level of 7,5% per one gram of pomelo peel and has very strong antioxidant potential